A curriculum and pedagogy for teaching problem analysis to first year students - Venable, John (AIS SIGED: IAIM, 2007)
This paper describes the rationale, curriculum, and pedagogy for a course focusing on problem analysis during Information Systems Development (ISD). Problem Analysis is concerned with eliciting, identifying, understanding, and reconciling the disparate perceptions and needs of different stakeholders for new or modified systems. To accommodate the needs of first year students, the course replaces the emphasis on theory that is common in more advanced courses with an emphasis on simple conceptual frameworks, extensive use of familiar (to first year students) examples, simple and straightforward processes, building up knowledge and skills through repetition, and collaborative group work.